Tree provenance affects the growth and bioenergy potential of juvenile silver birch - Haapala, Antti; Kontunen-Soppela, Sari; Oksanen, Elina; Rousi, Matti; Mola Yudego, Blas (Natural Resources Institute Finland, Luke, 2017)
The ever-growing need for renewable resources for energy production makes us look more closely at biomass reserves so far unused and considered insufficient in terms of energy content, availability or cost. In this study we present the first results of the calorific values and chemical composition of the branches of 12 micropropagated silver birch (Betula pendula) genotypes originating from 60°N to 67°N. The birches were planted at two different latitudes in Finland (62°N and 67°N) in a common garden experiment and harvested in juvenile stage during their fifth annual growth in Joensuu (62°N) in 2015 and during the sixth year in Kolari (67°N) in 2016. The results highlighted the calorific value ranges and their fair south-north gradient, while opposite trend was observed for the mass of branches upon harvest (green weight). The highest amount of extractives in branches was 15% w/w with methanol while water (13%) and acetone (10%) were also considered fairly efficient. Our preliminary results indicate that while the energy content and chemical composition vary by 12.5% along the latitudes of birch provenances, the most significant contribution to the available feedstock for bioenergy comes from branch quantity, being significantly higher in genotypes of southern latitudes grown in either of the common gardens. The indicated differences between the assessed genotypes based on preliminary description of data seem more profound in the trees grown in Joensuu (62°N)) than in Kolari (67°N)), possibly due to longer growing period and more substantial biomass yield in general able to differentiate between samples.